Arbuscular mycorrhiza improves nitrogen use efficiency in soybean grown under partial root-zone drying irrigation. Issue 2 (28th January 2019) - Liu, Hang; Song, Fengbin; Liu, Shengqun; Li, Xiangnan; Liu, Fulai; Zhu, Xiancan
ABSTRACT: Arbuscular mycorrhizal (AM) fungi can form symbiotic association with the roots of plants that acquire carbon (C) exclusively from the host plants and supply nitrogen (N) to the plants. In this study, our objective was to investigate the effects of the AM fungus on plant growth, C and N partitioning and accumulation of Glycine max L. grown under water stress in pot experiment. Soybean seedlings were inoculated or not inoculated with the AM fungus, and were exposed to three irrigation treatments including full irrigation, deficit irrigation and partial root-zone drying irrigation (PRD). The 15 N isotope labeling was used to trace soybean N accumulation. Results showed that water stress significantly decreased plant dry weight. Compared with non-AM fungus, AM fungus increased root N and 15 N concentration, and decreased stem, leaf and pod N and 15 N concentrations under PRD. AM colonization decreased C and N partitioning into stem and leaf, and increased C and N partitioning into root under PRD. AM plants had greater C accumulation and N use efficiency than non-AM plants. It was concluded that AM symbiosis plays an important role in C and N dynamics of soybean grown under water stress.